Dynamic analysis and verification of the motion of poultry eggs on supporting rollers. (March 2021) - Cheng, Ching-Wei; Chou, Yu-Chen; Li, Cheng-Han; Huang, Chien-Che; Weng, Yu-Kai
Abstract: Herein, a novel method is presented to establish equations for governing the motion of eggs on supporting rollers, enabling the usage of egg-classifying equipment as an important reference for optimally matching the forward speed and rotational speed of the egg and supporting rollers, respectively. The established theoretical equation was verified based on the screw lead theory and by performing real-world tests. Further, the differences between the theoretical and real speed values observed with respect to the obliquity angle of the egg and the egg shape index were analysed under identical supporting roller and rotating speed conditions. The deflection angle of the eggs rapidly increased during the initial 0–2 s but became stable thereafter. The real and theoretical speed values were similar when the egg shape index was approximately 78 and the obliquity angle was greater than 5°. The accuracy of the obtained theoretical velocity formula, which was verified using a support roller at a speed of 60 rpm, was confirmed based on the results of this study. In the future, the theoretical formula and experimental parameters can be derived based on this study. The length and speed of the roller can be adjusted, resulting in the delivery of eggs to the accurate position at the appropriate time using the automated grading and orientation equipment. Highlights: New approach to establish the equation of motion of eggs on supporting rollers. Theory of screw lead and real tests to verify and produce derived theoretical speed. Egg motion equation for air cell orientation development of egg product testing tools.